2018
DOI: 10.35627/2219-5238/2018-308-11-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Features of Modern Student Youth

Abstract: The results of the research show the main problems in the development of healthy lifestyle of modern student youth. We made the analysis of day regimen of modern students, identified the assessment of expertise level of balanced diet, found the frequency of use of the information-communication technologies different types for learning and leisure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Previously it was shown that more frequent and longer use of EAs changed life styles of contemporary schoolchildren and students, violating normal ratios of activities in their daily routines and influencing their health [24]; the situation seems alarming to hygienists and requires developing standards for ICT use by children, teenagers, and young people in their educational and leisure activities.…”
Section: T a B L Ementioning
confidence: 99%
“…Previously it was shown that more frequent and longer use of EAs changed life styles of contemporary schoolchildren and students, violating normal ratios of activities in their daily routines and influencing their health [24]; the situation seems alarming to hygienists and requires developing standards for ICT use by children, teenagers, and young people in their educational and leisure activities.…”
Section: T a B L Ementioning
confidence: 99%
“…На фоне неблагоприятной ситуации сохранение и укрепление здоровья детей и подростков всех возрастов является приоритетной государственной задачей [2]. Регулярная физическая активность необходима для нормального роста и развития детей и подростков и имеет ряд преимуществ для сохранения и укрепления здоровья [3][4][5]. Всемирная организация здравоохранения (ВОЗ) рекомендует, чтобы дети ежедневно занимались физической активностью, по крайней мере, по 60 минут [6].…”
unclassified
“…Характерной особенностью жизнедеятельности современных детей и подростков является малоподвижный образ жизни [3,7].…”
unclassified